2015
DOI: 10.1175/jtech-d-14-00192.1
|View full text |Cite
|
Sign up to set email alerts
|

Introducing an Approach for Extracting Temperature from Aircraft GNSS and Pressure Altitude Reports in ADS-B Messages

Abstract: Recently work has been conducted in using routine air traffic management (ATM) data from aircraft to derive meteorological observations (de Haan; de Haan and Stoffelen). The paper at hand introduces and provides an initial analysis for a method of finding layer temperatures from aircraft broadcast messages. The method is analyzed using error analysis and is shown capable of producing mean layer temperatures with below 61-K error with a layer thickness of 2000 m. Observed aircraft data have been compared to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…The derived temperatures are of lower quality due to the method of derivation de Haan (2011). Another method to derive temperature information has been developed by Stone and Kitchen (2015) where the height and pressure information available in Automatic Dependent Surveillance Broadcast (ADS-B) was exploited to estimate a mean-layer temperature. They found that a meanlayer temperature of a 2 km thick layer can be obtained with an error of around 1 K.…”
Section: Aircraft-derived Data (Mode-s Ehs)mentioning
confidence: 99%
“…The derived temperatures are of lower quality due to the method of derivation de Haan (2011). Another method to derive temperature information has been developed by Stone and Kitchen (2015) where the height and pressure information available in Automatic Dependent Surveillance Broadcast (ADS-B) was exploited to estimate a mean-layer temperature. They found that a meanlayer temperature of a 2 km thick layer can be obtained with an error of around 1 K.…”
Section: Aircraft-derived Data (Mode-s Ehs)mentioning
confidence: 99%
“…Stone and Kitchen () showed that a mean temperature for a layer of thickness 2,000 m could be computed using the global navigation satellite system's altitude reported by an aircraft's automatic dependent surveillance broadcast (ADS‐B) system. However, this method for determining thickness temperature is too coarse to resolve a temperature inversion.…”
Section: Introductionmentioning
confidence: 99%
“…However, de Haan (2011), Mirza et al (2016), Mirza (2017, table 6.2) and Stone (2017) suggest that the uncertainty in the derived temperature from a single aircraft at low levels can range between 2 and 10 K. This degree of uncertainty makes it difficult to locate the height and magnitude of the temperature inversion. Stone and Kitchen (2015) showed that a mean temperature for a layer of thickness 2,000 m could be computed using the global navigation satellite system's altitude reported by an aircraft's automatic dependent surveillance broadcast (ADS-B) system. However, this method for determining thickness temperature is too coarse to resolve a temperature inversion.…”
Section: Introductionmentioning
confidence: 99%
“…There are three types of reports from which meteorological observations may be obtained: Mode‐S EHS reports contain information on the aircraft's state vector. This vector can be used to derive estimates of the air temperature and horizontal wind at the aircraft's location (Collinson, ; de Haan, ). Mode‐S Meteorological Routine Aircraft Reports (MRAR) contain temperature and horizontal wind observations computed by the aircraft's FMS (Strajnar, ). Automatic Dependent Surveillance Broadcast (ADS‐B, a sub‐system of Mode‐S EHS) contain aircraft position and altitude from which a mean temperature and wind vector may be computed (de Leege et al , ; Stone and Kitchen, ). …”
Section: Introductionmentioning
confidence: 99%
“…(b) Mode-S Meteorological Routine Aircraft Reports (MRAR) contain temperature and horizontal wind observations computed by the aircraft's FMS (Strajnar, 2012). (c) Automatic Dependent Surveillance Broadcast (ADS-B, a sub-system of Mode-S EHS) contain aircraft position and altitude from which a mean temperature and wind vector may be computed (de Leege et al, 2012;Stone and Kitchen, 2015).…”
Section: Introductionmentioning
confidence: 99%